HUBUNGAN POLA MAKAN DENGAN KEJADIAN HIPERTENSI PADA LANSIA DIKELURAHAN BAHU LINGKUNGAN VI KECAMATAN MALALAYANG KOTA MANADO - Soloha, Marce (Journal Of Community & Emergency, 2024)
Diet is closely related to hypertension. If you eat unhealthy foods such as high fat, high sodium and high cholesterol, it will cause hypertension in a person, especially in the elderly. Because food can affect the rise or fall of blood pressure in a person. The purpose of this study was to determine the relationship between diet and the incidence of hypertension in the elderly. This study is a quantitative study using a cross-sectional method with a population of 84 and the number of samples 46 determined using the slovin formula. Collecting respondent data using questionnaire sheets and measuring blood pressure. Data analysis used the chi-square test statistical test with a value of 0.05. The results of the chi-square test test showed a P value of 0.00 so that the P value <0.05, then H0 was rejected and Ha was accepted, which means that there is a relationship between diet and hypertension. The conclusion of this study is that there is a relationship between diet and the incidence of hypertension in the elderly in Bahu Village VI, Malalayang District, Manado City.